Spatial targeting of woodland creation can reduce the colonisation credit of woodland plants - Samuel Hughes; William Kunin; Guy Ziv; Kevin Watts (Ecological Solutions and Evidence, 2023)
Abstract Colonisation credit refers to the temporal lag between positive conservation actions and species' responses and may be one of the reasons we fail to meet short‐term conservation targets. This is particularly evident in woodlands which take decades to develop and harbour slow colonising species. Given global objectives to increase woodland cover, it is important to know the timeframe within which colonisation credit will be fulfilled. The colonisation of woodland plants was examined in recent woodlands, created between 15 and 80 years ago, and located adjacent or isolated from existing ancient woodlands. Colonisation credit was calculated as the proportion of understory woodland plant species in the nearest ancient woodland which had not colonised recent woodlands. Looking at individual species traits also allowed us to tease apart their impact on the species colonisation and establishment ability. Spatial adjacency between created and ancient woodland reduced colonisation credit by an average of 28%, and more mature created woodlands (50–80 years old) had fulfilled 24% more of their colonisation credit on average than younger created woodlands (15–21 years old). However, mature woodlands created adjacent to ancient woodlands had still only been colonised by an average of 72% of the available species pool. Plants which had reached adjacent created woodlands were dispersed by a range of mechanisms, where those that had reached more isolated sites were largely dispersed by birds or mammals. Low community weighted mean shade tolerance, high community weighted nutrient affiliation, and the dominance of Hedera helix suggest that competition from dominant natives may be preventing certain species establishing in new woodlands. This research demonstrates the need to account for appropriate time‐lags when setting biodiversity targets, with most sites still displaying colonisation credit decades after they were created. The results also indicate that spatially targeting woodland creation adjacent to species‐rich mature woodlands should be prioritised. Still, poor local habitat conditions may lead to the dominance of specific competitors which prevent a range of other species from establishing. Local management interventions such as translocations and tree thinning may ameliorate this but further research is needed.